CBMT-29. PROMOTING FATTY ACID STORAGE BY DIACYLGLYCEROL-ACYLTRANSFERASE 1 PROTECTS GLIOBLASTOMA AGAINST OXIDATIVE STRESS AND MAINTAINS LIPID HOMEOSTASIS FOR RAPID TUMOR GROWTH. (11th November 2019) - Cheng, Xiang; Geng, Feng; Zhong, Yaogang; Tian, Zhihua; Pan, Meixia; Cheng, Chunming; Horbinski, Craig; Mo, Xiaokui; Han, Xianlin; Guo, Deliang
Abstract: Fatty acids are essential building blocks and energy substrates of lipids in cells. They constitute the major structural components of membrane lipids, i.e., glycerophospholipids and sphingolipids, and also serve as an important energy resource. Whereas excess fatty acids or dysregulation of fatty acid metabolism causes lipotoxicity, leading to severe cell damage. We previously identified that lipid metabolism is dramatically altered in glioblastoma (GBM), especially fatty acid synthesis, which is greatly elevated in various types of cancers. However, how tumor cells prevent excessive fatty acids accumulation from inducing lipotoxicity has rarely been studied. We recently identified that GBM greatly upregulates diacylglycerol-acyltransferase 1 (DGAT1) to direct excess fatty acids into triglycerides and lipid droplets to prevent oxidative stress. Inhibiting DGAT1 disrupts lipid homeostasis and shifts excessive fatty acids moving into mitochondria for oxidation, resulting in a high level of reactive oxygen species (ROS), mitochondrial damage, cytochrome c release and apoptosis. Inhibiting carnitine palmitoyltransferase to reduce fatty acids shuttling into mitochondria significantly decreases ROS and rescues cell death caused by DGAT1 inhibition. Xenograft models show that genetic or pharmacological inhibition of DGAT1 blocks lipid droplet formation, induces tumor cell apoptosis and markedly suppresses GBM tumor growth. Together, our study demonstrates that DGAT1 upregulation protects GBM from oxidative damage and maintains lipid homeostasis by facilitating excess fatty acids storage. Our data further show that targeting DGAT1 specifically induces lipotoxicity in tumor cells, while sparing normal brain, which is a very promising therapeutic strategy antagonizing GBM and has a high potential to shift current paradigm in treating GBM.